Effect of the ankle stabilizing orthosis on foot and ankle kinematics during cutting maneuvers - Gudibanda, A.; Wang, Y. T. (Research in Sports Medicine, 2005)
This study was to examine the stability and functionality of the Ankle Stabilizing Orthosis (ASO) in normal ankle kinematics during sideward and forward lateral cutting. Fifteen college students with normal ankles were randomly assigned to each of the following four conditions: sideward and forward lateral cutting, with and without the ASO. Ankle inversion-eversion and dorsiflexion-plantarflexion angular displacements and velocities during movement were recorded by a 3-D Qualisys system and analyzed with repeated measures ANOVA and Bonferroni test. In forward lateral cutting, the ASO decreased inversion angle at touchdown. On both lateral cutting conditions, the ASO decreased inversion angle at footflat and push-off, and decreased plantarflexion angle at touchdown. Furthermore, the ASO did not change inversion-eversion and dorsiflexion-plantarflexion angular velocities or stance phase duration. The ASO is likely to prevent ankle sprains during activities that involve lateral cutting while not hindering athletic performance. Information presented may help clinicians in brace prescription.